Boards of directors and performance in autonomous public sector entities. Issue 2 (17th February 2023) - Garcia-Lacalle, Javier; Royo, Sonia; Yetano, Ana
ABSTRACT: The adoption of business-like boards of directors in the public sector has to be evaluated in terms of financial and non-financial outcomes. This paper investigates, using a structural equation model, the relationship of certain board characteristics with the performance of English NHS foundation trusts. Larger and more independent boards do not harm performance. Having a woman chairing the board is related to better service quality. Boards seem to be more concerned about service quality issues than about financial problems.